Psychosocial Stress Induces Schizophrenia-Like Behavior in Mice With Reduced MMP-9 Activity - Vafadari, Behnam; Mitra, Shiladitya; Stefaniuk, Marzena; Kaczmarek, Leszek (Frontiers in Behavioral Neuroscience, 2019)
Understanding gene¬-environment interactions in the pathogenesis of schizophrenia remains a major research challenge. Matrix metalloproteinase-9 (MMP-9) has been previously implicated in the pathophysiology of schizophrenia. In the present study, adolescent Mmp-9 heterozygous mice, with a genetically lower level of MMP-9, were subjected to resident-intruder psychosocial stress for 3 weeks and then examined in behavioral tests that evaluated cognitive deficits and positive- and negative-like symptoms of schizophrenia. Cognitive and positive symptoms in unstressed Mmp-9 heterozygous mice were unaffected by stress exposure, whereas negative symptoms were manifested only after stress exposure. Interestingly, negative symptoms were ameliorated by treatment with the antipsychotic drug clozapine. We describe a novel gene  environment interaction mouse model of schizophrenia. Lower MMP-9 levels in the brain might be a risk factor for schizophrenia that in combination with environmental factors (e.g., psychosocial stress) may evoke schizophrenia-like symptoms that are sensitive to antipsychotic treatment.